Financial Institutions and Markets across Countries and over Time - Beck, Thorsten (World Bank, 2012)
This article introduces the updated and expanded version of the Financial Development and Structure Database. The database includes indicators on the size, efficiency, and stability of banks, nonbank financial institutions, and equity and bond markets over 1960–2007. It also contains indicators of financial globalization.